1995
DOI: 10.1007/bf00058205
|View full text |Cite
|
Sign up to set email alerts
|

Permanent seed banks in chalk grassland under various management regimes: their role in the restoration of species-rich plant communities

Abstract: A survey was carded out on four stands of a chalk grassland (open, intensively grazed, tall and scrub) in order to monitor the permanent soil seed bank under various management regimes responsible for the decline of the ecological interest of this ecosystem. There was no real similarity between the seed banks and the associated vegetation, except in the intensively grazed stand. When vegetation changes, seed banks appear to be quite stable and are mostly dominated by three species ( Centaurium erythraea, Origa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 32 publications
(33 reference statements)
4
39
0
Order By: Relevance
“…It seems that xerothermic and thermophilous species colonize restored plots mainly in a vegetative way or as seed rain (Jefferson and Usher 1987;Willems and Bik 1998). The seed bank plays a rather insignificant role in restoration of species-rich xerothermic grasslands (Barbaro et al 2001;Dutoit and Alard 1995;Davies and Waite 1998). Many studies on seed banks have shown the disparity between the species composition of the seed bank and the above-ground vegetation (Chippindale and Milton 1934;Graham and Hutchings 1988).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems that xerothermic and thermophilous species colonize restored plots mainly in a vegetative way or as seed rain (Jefferson and Usher 1987;Willems and Bik 1998). The seed bank plays a rather insignificant role in restoration of species-rich xerothermic grasslands (Barbaro et al 2001;Dutoit and Alard 1995;Davies and Waite 1998). Many studies on seed banks have shown the disparity between the species composition of the seed bank and the above-ground vegetation (Chippindale and Milton 1934;Graham and Hutchings 1988).…”
Section: Discussionmentioning
confidence: 99%
“…As is shown in Figure 4, some xerothermic species, such as: Origanum vulgare and Hypericum perforatum, which colonise restored plots, are an exception. These species are usually main components of the persistent seed bank from which they regenerate after disturbances (Grime 1990(Grime , 2001Dutoit and Alard 1995). Apart from xerothermic grassland, they are often encountered in anthropogenic plant communities, which develop on roadsides and escarpments with similar habitat conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the long-term, continuous disturbance (e.g. overgrazing) can lead to local extinction of plant species (O'Connor, 1991), and can result in almost irreversible changes in vegetation, whereby a return to previous conditions from the soil seed bank is prevented (Dutoit and Alard, 1995;Kinloch and Friedel, 2005a;Meissner and Facelli, 1999). Therefore, a key factor in sustainable resource management is resting, which might be more important than the way rangelands are utilized (Snyman, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…When grazing is ceased the dispersal of most grassland species is limited to several metres or even to several dozen centimetres (VERKAAR et al 1983;STAMPFLI, ZEITER 1999;KALAMEES, ZOBEL 2002). Species-rich grasslands cannot be restored from soil seed bank because relatively few species of these communities form persistent seed bank in the soil, and seeds of many grassland species have a short life span in soil (DUTOIT, ALARD 1995;BEKKER et al 1997;WILLEMS, BIK 1998;STAMPFLI, ZEITER 1999). Experimental studies suggest that even though the seeds of grassland species do occur in seed rain or soil seed bank, successful restoration of species-rich grasslands may still require additional management such as grazing or mowing in order to facilitate the development of suitable species seedlings (HUTCHINGS, BOOTH 1996).…”
Section: Changes In Calcareous Grassland Vegetation and Management Fomentioning
confidence: 99%